TEACHER COMPETENCES IN THE SPHERE OF E-LEARNING - KNYCH, Aleksandra (Journal of Technology and Information Education, 2012)
Along with the development of the Internet the popularity of distant learning (e-learning) soared. E-learning is based on a concept of student self-study and teacher didactic care and guidance. E-learning poses a challenge for today's teacher, who should be characterized by suitable competences.
Keywords: e-learning; e-teaching; competences